Numerical analysis on effect of support engineering on flame propagation from gas explosion accident in mining. Issue 8 (2nd November 2015) - Pang, Lei; Liu, Lei; Kang, Yong; Lv, Pengfei
Abstract : Purpose: – Gas explosion is one of the most major types of accident in mining projects, and the flame front with high temperature is major hazardous factor induced by this kind of accident. Support engineering provides an available way to solve problems related to ground movements, but very likely has a great influence on the gas explosion accident process, especially the flame propagation, and then aggravates mining risk. However, until now it has not been received much attention from scientific works. The paper aims to discuss these issues. Design/methodology/approach: – A commercial CFD software package AutoReaGas suitable for gas explosion is used to carry out the numerical investigation of gas explosion process in a straight coal tunnel with typical support engineering, especially the unsteady explosion field and the flame propagation process in it. Findings: – Support engineering composed by multiple bars take positive influence on flame acceleration: the flame speed is much faster than that under no support bars, and the smaller support spacing induces greater flame speed near the ignition. The support bars also exert negative influence on flame acceleration: the larger support spacing induces greater flame speed in most region of the tunnel. Furthermore, a traditional viewpoint that denser obstacles induce greater explosion effects is one-sided according to this study. Originality/value: – At present, no one concerns the aggravating influence of support engineering on accident risk in practical mining projects because of small geometric dimension. This work examines the effect of steel support system on evolution processes of gas explosion accidents, especially the flame propagation. The conclusions provide quantitative scientific basis for this kind of the accidents in risk evolution and accident investigation of mining engineering.